Faktor-Faktor yang Berpengaruh Terhadap Kinerja Usaha Wanita Wirausaha Kerupuk Udang di Provinsi Jambi - Martauli, Elvin Desi; Baga, Lukman M.; Fariyanti, Anna (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
The purpose of this research is to analyze the relationship of personal characteristics on the entrepreneurial behavior and factors affecting the business performance of prawn crackers women entrepreneurs in Jambi Province. This study was conducted using a survey in two regencies in the Jambi Province. The method of analysis used in the study is Structural Equation Modelling (SEM) with Partial Least Square (PLS) approach. The results shows i) training, business experience, education, and family background positively significant affect to the entrepreneurial behavior (including motivation, innovation and risk taking decision); ii) business performance is influenced by personal characteristics, entrepreneurial behavior, internal environment and the external environment. Personal characteristic of women entrepreneur on prawn crackers business in Jambi Province is the most influence factor on woman business performance.